Growth and Sexual Dimorphism of the Hyoid Body in Macaca mulatta - Cunningham, Andreana S. (International journal of primatology, 2020)
The hyoid contributes to a range of functional behaviors such as breathing, swallowing, and vocalization. Among nonhuman primates, hyoid morphology and position show taxonomic differences. For example, cercopithecoid hyoids are more anatomically constrained than hominoid hyoids, which may influence their morphology. While most of the existing literature on the hyoid in nonhuman primates compares morphological differences among species, studies of intraspecific hyoid morphological variation are scarce. This study used a geometric morphometric approach to examine the effects of age and sex on hyoid morphology in Macaca mulatta . The sample comprised 154 skeletal specimens housed at the University of Puerto Rico’s Caribbean Primate Research Center, representing both sexes and an age range of 1–25 years old. I collected three-dimensional landmark coordinate data from the cranium, mandible, and hyoid body of each specimen and tested the effects of age and sex on hyoid morphology through principal components analysis and full factorial analyses. Hyoid shape correlated strongly with age but not sex. Hyoid shape and size correlated strongly with both life history stage and age class. While the hyoid appears to grow within expected body size parameters, hyoid morphology is not fully isometric. Rather, the hyoid exhibits superoinferior lengthening and upward rotation through postnatal ontogeny, with notable upward rotation of the superior surface occurring at 1–4 years of age. As maturational processes such as vocal tract lengthening impose age-linked constraints on vocal behavior, these findings suggest that the hyoid grows in relation to surrounding vocal tract anatomy, and that hyoid shape may contribute to structural support for age-linked vocalization.